Strategi Bisnis Thrifting / Lelong Di Masa Pandemi: Strategi Bisnis - yekti Purwo Asih (J-MD Jurnal Manajemen Dakwah, 2022)
Thrifting/Used Goods Business Strategy in a Pandemic Period. Department of Da'wah Management. Faculty of Usuludin Adab and Da'wah. Thrifting or used goods business alias auction is a fairly popular business in Pontianak, West Kalimantan. The problem that will be studied here is about how auctioneers sell their wares during this pandemic so that there are no significant losses. The method that the author uses to make this paper by using the method of observation and literature. This research was conducted in order to find out the trading strategies of auctioneers in a time that could be said to be very difficult to interact directly with humans. Keywords: Strategy, Business, Secondhand, Pandemic, Covid-19